Notifications of Covid-19 and Its Potential Impacts for Readers: A Study of Critical Discussion Case Study of the Antara and Republika Media - Fikri Hakim; Shinta Rosiana; Dede Wahyu Firdaus; Ai Siti Nurjamilah (Budapest International Research and Critics University, 2022)
The media's point of view on an issue has a considerable impact on reader acceptance and understanding. This is the background for researchers to study further about the media's point of view. This study aims to identify the media's point of view between Antara and Republika in reporting on COVID-19. The researcher chose the Covid-19 news as the object of study because currently the issue is a global issue and of course has a high level of urgency to be studied further. There are six discourses that become sources of data analysis. This study uses a qualitative method with a critical discourse study approach of Teun A. van Dijk. The researcher uses three elements of van Dijk's textual analysis, namely thematic elements, intent, and quotations. The results of the textual analysis are combined with an analysis of the social and cultural background of the media. An analysis of the social and cultural setting of the media was carried out to identify the potential influence of this setting on the news production process. The results of the analysis show that the news on Covid-19 in the Antara media tends to bring the state (government) point of view, while Republika is more from a general point of view.